Neuroprotective Effect Of Papaya (Carica papaya L.) Leaf Extract In Pyramidal Cells Of Hippocampus And Cerebral Cortex In Trimethyltin-Induced Mice (Mus musculus L.) - Masnunah, Siti; Wiratmini, Ngurah Intan; Suarni, Ni Made Rai (Metamorfosa: Journal of Biological Sciences, 2020)
This study aimed to determine the histological features of the hippocampus and cerebral cortex of mice ( Mus musculus L.) that induced by TMT which is given papaya leaf extract ( Carica papaya L.) and to determine the optimum dose of neuroprotective papaya leaf extract.The study used a Completely Randomized Design (CRD) with five treatments consisting of K+ (only TMT-induced at a dose of 0,6 mg/kgBW), K- (only given Na-CMC 0.5%), P1 (TMT-induced and given papaya leaf extract dose of 500 mg / kgBW) , P2 (TMT-induced and given papaya leaf extract at a dose of 1000 mg/kgBW), P3 (TMT-induced and given papaya leaf extract at a dose of 2000 mg/kgBW). The parameters observed were pyramidal cell necrosis and the percentage of pyramidal cells damage in the hippocampus and cerebral cortex. The results showed a decrease in the percentage of pyramidal cell damage in the hippocampus at P1 by 26,46%, P2 by 28,91%, and P3 by 26,67%. The percentage of pyramidal cell damage in the cerebral cortex decreased in P1 by 9,62%, P2 by 11,14%, and P3 by 14,88%. The optimum dose of papaya leaf extract which is neuroprotective is 2000 mg/kgBW (P3).   Keywords : papaya leaf, TMT, neuroprotective, necrosis, cerebrum, hippocampus